Non-catalytic pyrolysis of scrap tires using a newly developed two-stage pyrolyzer for the production of a pyrolysis oil with a low sulfur content. (15th May 2016) - Choi, Gyung-Goo; Oh, Seung-Jin; Kim, Joo-Sik
Highlights: Scrap tire rubber was successfully pyrolyzed in a two-stage pyrolyzer. The two-stage pyrolyzer is composed of auger and fluidized bed reactors. N2 and temperatures of ∼500 °C were effective for a low-sulfur oil. A pyrolysis oil contained only 0.55 wt.% of sulfur and 0.28 wt.% of nitrogen. A pyrolysis oil from the auger reactor contained 50 wt.%d l -limonene. Abstract: The aim of this work was to reduce the sulfur content of pyrolysis oil derived from the scrap tire pyrolysis. In this respect, a series of pyrolysis experiments was conducted in both a fluidized bed reactor (one-stage pyrolysis) and a newly developed two-stage pyrolyzer consisting of an auger reactor and a fluidized bed reactor in series (two-stage pyrolysis). The one-stage pyrolysis was carried out at ∼500 and 600 °C with different fluidizing gases (N2 and product gas). In the experiments, the pyrolysis oil obtained at ∼500 °C had a lower sulfur content than that produced at ∼600 °C. N2 was better at producing a low-sulfur pyrolysis oil than product gas. The sulfur contents of the oils obtained from the one-stage pyrolysis ranged from 0.75 to 0.92 wt.%. The two-stage pyrolysis was conducted using product gas as the fluidizing medium at different auger reactor temperatures (∼230–450 °C) and at a constant fluidized bed reactor temperature (∼510 °C). A pyrolysis oil containing only 0.55 wt.% of sulfur could be produced at the temperatures of the auger reactor of ∼330 °C and fluidized bed reactor of ∼510 °C. Moreover, the two-stage pyrolysis could produce an oil with a low nitrogen content (0.28 wt.%). A pyrolysis oil obtained from the auger reactor containedd l -limonene up to 50 wt.%.